The Removal of HBV in Plasma by Extracorporeal Immunoadsorption from Plasma: A Potential Therapy of Hepatitis B Patients. (23rd December 2018) - Han, Zhenwei; Lu, Xuan; Tang, Yiping; Yang, Yuanyuan; Liu, Qiuchen; Cheng, Pengfei; Zhou, Li; Wang, Yefu
Abstract : Objective . To establish a novel HBV specific immunoadsorbent for the removing of HBV particles. Methods . The anti-HBsAg monoclonal antibody was immobilized on sepharose beads to produce a sepharose anti-HBs column. Then the immunoadsorbent was evaluated and characterized by scanning electron microscopy. In addition, time-dependent effects of the eradication capacity of anti-HBsAg functionalized sepharose beads against HBV were investigated. Results . Proposed immunoadsorbents exhibited a favorable biocompatibility as well as specificity. With the optimized recycle time, the decontamination performance of HBV particles and quantity of HBsAg were assessed either by real-time quantitative PCR or ELISA, which showed that the immunoadsorbent could remove approximately 90% of the HBV and 90% of the HBsAg from human plasma samples. Conclusions . All these results indicated that the novel immunoadsorbent could effectively remove HBV particles and likely serve as a novel therapy option or at least supplementary for the treatment regimen of HBV.